The FORMULATION AND ACTIVITY TEST OF GEDI LEAF (Abelmoschus manihot L.) ANTI-ACNE GEL ETHANOL EXTRACT ON Staphylococcus aureus IN VITRO - Suleman, Abdul Wahid (Jurnal Penelitian Farmasi & Herbal, 2023)
Gedi leaves (Abelmoschus manihot L.) have compounds such as flavonoids, saponins, tannins, and terpenoids which are useful as antibacterials, such as the treatment of acne and other diseases. This research method was carried out in a laboratory experiment, namely gedi leaf extract was made in the form of a gel preparation with a concentration of negative control, FI (2.5%), FII (5%), FIII (7.5%) . Then proceed with the evaluation of the preparation with the organoleptic test, homogeneity test, pH test, spreadability test, adhesion test, viscosity test, and Cyling test. Antibacterial activity testing was carried out using the well method. The results of this study indicate that the ethanol extract of gedi leaves can be formulated as an anti-acne gel preparation that is physically and chemically stable. In the antibacterial test, the inhibition zone formed in formula 1 (2.5%) was 10,7±0,95 mm, in formula 2 (5%) the inhibition zone formed was 15,6±0,86 mm and in formula 3 (7.5%) was the concentration which has the most optimal antibacterial activity against Staphylococcus aureus bacteria with an inhibition zone area of 18,8±0,70 mm. Conclusion: Gedi leaf ethanol extract anti-acne gel preparation can inhibit Staphylococcus aureus bacteria most effective at a concentration of 7.5%, namely 18,8±0,70 mm